Tendensi Penerapan Sikap Sami’na Wa Atho’na Mahasiswa Perbankan Syariah dalam Mempengaruhi Sikap Profesionalisme sebagai Praktisi - Syfa'ul Mu'akhiro; Andriati Aziizah Syafitri (Universitas Islam Raden Rahmat, 2025)
Sami'na wa atho'na is a sentence that is often heard and said in everyday life, especially in Islamic boarding school environments. Apart from sami'na wa atho'na, professionalism is an attitude that also has an influence in the work environment. If sami'na wa atho'na is applied in the work environment without professionalism, it will result in poor human resources. Both are equally important to improve employee performance in a company. This research aims to determine the implementation of the sami'na wa atho'na attitude of sharia banking students in depth which is inherent in each individual. And aims to determine the impact that occurs if this attitude is continuously practiced in financial institutions. The object of this research is the Mini Syariah Bank Khaira Ummah, Raden Rahmat Islamic University, Malang. This type of research uses qualitative research using data collection methods, namely observation, interviews and documentation. The results of this research show that Bank Mini Syariah employees have implemented a sami'na wa atho'na attitude and are also accompanied by high professionalism, thus making good human resources, which are in accordance with Islamic sharia rules. The suggestion put forward in this research is that this research can be used as a means of education regarding the influence of the sami'na wa atho'na attitude and professionalism, as well as being a motivation for readers to apply the sami'na wa atho'na attitude and professionalism in their daily lives, especially in the workplace.